“OMO T’O MO ‘YA’RE LOJU” (A child that despises his mother) narratives cultural value of motherhood in Jimi Solanke’s music - Omotoso, Gbenga; Adekogbe, Olatunbosun Samuel; Daramola, Olusanjo Mathew Abayomi (Journal of Gender and Power, 2020)
Within the traditional African setting, the values of an African mother in the domestic and societal ambience have called for great concerns. Akinjobi (2011, p. 2) examines African Motherhood as a sacred as well as a powerful spiritual component in the nurturing and development of an African child. The scope of this paper therefore, is to examine the position of Jimi Solanke on the values of African mothers as advocated in some of his purposively selected songs which address the values and position of motherhood as caretakers of children and strongholds in African homes. The paper adopts oral interview, the theory of Womanism and Feminism as rightly observed by Sotunsa (2008, pp. 227–234) as its methodological approaches and largely concentrates on the experience of an African mother, the family relationship as well as the importance of motherhood in her role as an African child nurturer and developer. The paper finds out that Jimi Solanke has not only appraised the values of African mothers, but also expressed severe consequences on any African child who despised or despoiled an African mother.